Analysis of parameters in electrocardiographic signals of patients with Chagas and time domain variables of the HRV using high resolution polygraph (Orinoquia, 2019)
This paper presents the results obtained from a study on the analysis of electrocardiographic parameters in records of patients seropositive to Chagas disease of the Department of Meta and measurement of the variables in the time domain of heart rate variability (HRV) and its comparison with population control records. A total of 38 10-minute records were obtained in the vast majority (57.9%) with a high resolution polygraph between both populations, creating an annotated database of these records. The present study allowed us to find significant differences in electrocardiographic parameters for the QTc interval between the groups, which could be a consequence of an alteration of the cardiac conduction that translates into a greater increase in the QTc, as well as the affectation of the time domain variables of Heart Rate Variability (HRV), such as the SDRR and SEHR, which result in lower values for HRV-positive patients with Chagas disease. It is concluded that variables from the ECG and HRV registries present an alteration in patients with Chagas disease, which could be used as early warnings of the serologically undiagnosed disease.
Keywords: Chagas disease; electrocardiographic parameters; heart rate variability (HRV); QTc interval